Evaluación de las preferencias del cliente en lo relacionado al uso de los productos y servicios financieros que oferta el Banco Pichincha Agencia Loja, en el periodo septiembre 2016 a septiembre 2017 - Cueva Pesantez, Galo Fabricio (2018)
The main objective of the research is to evaluate the preferences of the client when selecting a product or service in the Banco Pichincha Loja Agency, during the period September 2016 September 2017, in order to provide the institution with information that helps in decision-making for its strengthening. The investigative process is descriptive, since it deals with the characteristics of the problem under study and its consequent fulfillment of objectives; for which methods, techniques and procedures were used necessary in order to identify the preferences of customers in the selection of products and services offered by the financial institution. In the perspective of fulfilling the general objective, each of the specific objectives was developed; Firstly, the compilation of information on the products and services granted by Banco Pichincha Agencia Loja was carried out, during the study period, a survey was subsequently applied to know the preferences of the users and thus establish how this has impacted offer in the living conditions of customers. The results generated from the fulfillment of the specific objectives, allowed to identify the different products and services of the national financial system, through which Banco Pichincha Loja Agency provides services, establish the factors that influence the client for the use of said offer, and perform an assessment of the quality of both products and services, as well as customer service during the period September 2016 to September 2017. Finally, it is established that Banco Pichincha Agencia Loja, through the financial products and services offered, has contributed positively to the socioeconomic development of its beneficiaries